2009
DOI: 10.1088/1674-4527/9/1/006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-correlations between 21 cm, X-ray and infrared backgrounds

Abstract: The history of the cosmological reionization is still unclear. Two ionizing sources, stars and QSOs, are believed to play important roles during this epoch. Besides the 21 cm signals, the infrared emission from Pop III stars and X-ray photons from QSOs can be powerful probes of the reionization. Here we present a cross-correlation study of the 21 cm, infrared and X-ray backgrounds. The advantage of doing such crosscorrelations is that we could highlight the correlated signals and eliminate irrelevant foregroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…The 21 cm and SXB backgrounds become anticorrelated after the equilibration phase. The crossover scale mentioned by Shan & Qin (2009), corresponding to the characteristic bubble size, is indistinct in all of our models. But we can find a marked trough in the power spectrum after the equilibration phase in the fiducial model.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The 21 cm and SXB backgrounds become anticorrelated after the equilibration phase. The crossover scale mentioned by Shan & Qin (2009), corresponding to the characteristic bubble size, is indistinct in all of our models. But we can find a marked trough in the power spectrum after the equilibration phase in the fiducial model.…”
Section: Resultsmentioning
confidence: 74%
“…In this paper, we use a modified version of the seminumerical simulations, the 21CMFAST, to investigate the evolution of the 21-SXB cross angular power spectra during the EoR. The 21-SXB cross power spectra have been studied by Shan & Qin (2009). Combining data from LOFAR and ROSAT in an analytic model, they found that although the cosmic 21 cm signals could be detected, the 21-SXB power spectra are still limited by noise in the ROSAT surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are also expected to contribute to the CXB, it is not possible to separate such components directly from the CXB measurements due to the lack of redshift information. Since these sources are usually hosted in very dense regions, they are expected to anti-correlate with the 21 cm signal originating from the neutral hydrogen found further away from the production sites of ionizing photons (Shan & Qin 2009;Liang et al 2016). Exploiting the redshift information offered by the 21 cm signal, such cross-correlation could then be used to give information on the properties of the X-ray sources during the EoR, as well as confirm the origin of the 21 cm signal.…”
Section: Introductionmentioning
confidence: 99%
“…These simulations are used to evaluate the 21 cm signal and the cross-correlation with the CXB for several source models. As mentioned above, such correlations were previously investigated by Shan & Qin (2009) by means of two semi-analytic models for reionization (stars dominated or quasars dominated), and by Liang et al (2016) using semi-numerical 21CMFAST simulations which included three cases of X-ray emitting efficiency. Both works concluded that a cross-correlation between X-ray background and 21 cm signal exists, although it is difficult to measure.…”
Section: Introductionmentioning
confidence: 99%
“…Cappelluti et al 2012). While the high-z component might be less than a few percent (Ma et al 2018a), the 21 cm line and X-ray background (XRB) CC can be a useful tool to reveal the XRB source as suggested in Shan & Qin (2009); Liang et al (2016); Ma et al (2018a). In Ma et al (2018a), they studied the CC using radiative transfer simulation (Eide et al 2020).…”
Section: Cosmic Microwave Background Near Infraredmentioning
confidence: 99%